Объяснение:
12x²-4x-1=4
12x²-4x-5=0
D= 16+240=256
x1= (4-16)/24= -12/24= -0,5
x2= (4+16)/24= 5/6
По условию, необходимо решить следующее уравнение:
12x²-4x-1 = 4
12x²-10x+6x-5 = 0
2x(6x-5)+(6x-5) = 0
(6x-5)(2x+1) = 0
6x-5=0 или 2x+1=0
или
ответ: -0,5; 5/6.
Объяснение:
12x²-4x-1=4
12x²-4x-5=0
D= 16+240=256
x1= (4-16)/24= -12/24= -0,5
x2= (4+16)/24= 5/6
По условию, необходимо решить следующее уравнение:
12x²-4x-1 = 4
12x²-10x+6x-5 = 0
2x(6x-5)+(6x-5) = 0
(6x-5)(2x+1) = 0
6x-5=0 или 2x+1=0
ответ: -0,5; 5/6.